Effect of temperature variation and strain rate on the mechanical properties of multi-material lattice structures - Parham Mostofizadeh; Robert A. Dorey; Iman Mohagheghian (Materials & Design)
Multi-material additive manufacturing has emerged as a promising avenue for the creation of innovative metamaterials including multi-material lattices with unique characteristics. This paper presents the examination of the impacts of varying loading rate and temperature on the mechanical properties of such lattice structures. The primary objective is to enhance understanding of how manipulating materials’ configurations within multi-material lattices (by employing materials with different strain rate and temperature sensitivities) affects overall mechanical characteristics. The multi-material design was found to provide a broader and more tunable range of properties, e.g. peak stress increase of over 80 % with changing strain rate from 10−4 to 10−2 s−1 in comparison to a 30 % increase for the single-material design and a 96 % drop in peak stress, compared to an 84 % decrease for the single-material design when changing temperature from 27 °C to 50 °C. Results indicate that through multi-material design, post-elastic deformation can be finely tuned for specific application requirements, whether necessitating high stiffness or high energy absorption. Moreover, it is observed that the global strain rate sensitivity of the multi-material lattice is influenced not only by the intrinsic sensitivity of constituent materials but also by the changes in local stress and strain distribution as the rate increases.